2013
DOI: 10.5194/tc-7-67-2013
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of present and future seasonal Northern Hemisphere land snow cover simulated by CMIP5 coupled climate models

Abstract: Abstract. The 20th century seasonal Northern Hemisphere (NH) land snow cover as simulated by available CMIP5 model output is compared to observations. On average, the models reproduce the observed snow cover extent very well, but the significant trend towards a reduced spring snow cover extent over the 1979-2005 period is underestimated (observed: (−3.4 ± 1.1) % per decade; simulated: (−1.0 ± 0.3) % per decade). We show that this is linked to the simulated Northern Hemisphere extratropical spring land warming … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 44 publications
12
129
0
Order By: Relevance
“…Recently, Brutel-Vuilmet et al (2013) found that, while there is still substantial intermodel dispersion among the CMIP5 models, on average the springtime snowmelt is slightly delayed in northern Eurasia. Taken at face value, the default version of ECHAM5 agrees with this result for the eastern parts of northern Eurasia, while in the west, snow vanishes too early (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Brutel-Vuilmet et al (2013) found that, while there is still substantial intermodel dispersion among the CMIP5 models, on average the springtime snowmelt is slightly delayed in northern Eurasia. Taken at face value, the default version of ECHAM5 agrees with this result for the eastern parts of northern Eurasia, while in the west, snow vanishes too early (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…These include several intercomparisons of snow conditions simulated by atmospheric and fully coupled general circulation models (GCMs) with observational data (Foster et al, 1996;Frei and Robinson, 1998;Frei et al, 2003Frei et al, , 2005Roesch, 2006;Derksen and Brown, 2012;Brutel-Vuilmet et al, 2013). Most recently, Brutel-Vuilmet et al (2013) evaluated the snow cover simulated by models participating in Phase 5 of the Coupled Model Intercomparison Project (CMIP5).…”
Section: P Räisänen Et Al: Snow-off Timing In Echam5mentioning
confidence: 99%
See 1 more Smart Citation
“…A standard target for snow process analysis in climate models is snow-cover extent trends, which are strongly temperature 25 controlled (e.g. Brutel-Vuilmet et al, 2013;Mudryk et al, 2017). Assessing the ability of models to capture these trends needs to account for natural variability, forced variability, observational uncertainty, and intermodel differences.…”
Section: Canesm2 Climatology and Trendsmentioning
confidence: 99%
“…Brutel-Vuilmet et al (2013) have compared the 20th century seasonal northern hemisphere land snow cover as simulated by available CMIP5 model output to observations, and the results show that the models reproduce the observed snow cover extent very well on average but the significant trend toward a reduced spring snow cover extent over the 1979-2005 period is underestimated. Zhu and Dong (2013) have pointed out that the CMIP5 coupled models can catch the main distribution characteristics of the observed northern hemisphere March-April snow cover but overestimate the mean snow cover in complex terrain area such as Qinghai-Tibet Plateau.…”
Section: Introductionmentioning
confidence: 99%